2019
DOI: 10.1101/591776
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hierarchy of connectivity-function relationship of the human cortex revealed through predicting activity across functional domains

Abstract: Many studies showed that anatomical connectivity supports both anatomical and functional hierarchies that span across the primary and association cortices in the cerebral cortex.However, it remains unclear whether a hierarchy of connectivity-function relationship (CFR) exists across the human cortex as well as how to characterize the hierarchy of this CFR if it exists. We first addressed whether anatomical connectivity could be used to predict functional activations across different functional domains using mu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 60 publications
(72 reference statements)
0
12
0
Order By: Relevance
“…35 In addition, it is expected that white matter disruption induces functional changes at the cortical level. 36 Therefore, we performed a complementary analysis aimed to integrate functional and structural maps. We defined significant functional regions and adjacent white matter voxels as seeds for tractography in the seed tracking algorithm provided by DSI Studio (http://dsi-studio.labsolver.…”
Section: Functional Connectivity Analysismentioning
confidence: 99%
“…35 In addition, it is expected that white matter disruption induces functional changes at the cortical level. 36 Therefore, we performed a complementary analysis aimed to integrate functional and structural maps. We defined significant functional regions and adjacent white matter voxels as seeds for tractography in the seed tracking algorithm provided by DSI Studio (http://dsi-studio.labsolver.…”
Section: Functional Connectivity Analysismentioning
confidence: 99%
“…Among these connectivity-based methods, functionalfingerprint-based methods are dominant and direct in the cerebral cartography, providing a lot of perspective and practical works for the clinics [13,37,40]. On the other side, structure covariations and anatomical fingerprints could reflect the individual functional variability to some extent [29,42,66], but are still less investigated and involved in the brain atlas individualization. The anatomical fingerprints have the advantages in reproducibility in many studies, compared with functional fingerprints [66].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies showed there exists a structure-function relationship and the identification of functional area through anatomical fingerprint [28,29,47,48]. In this study, the fibertract-based connectivity fingerprint was calculated, as the one of input in the graph convolutional network (shown in Fig.…”
Section: B Connectivity Fingerprints Of Fiber-tract Embeddingmentioning
confidence: 99%
See 1 more Smart Citation
“…The connectivity profile can be defined in terms of the white matter pathway represented by tractography through diffusion magnetic resonance imaging (MRI), or in terms of the temporal coupling between spontaneous fluctuations of resting-state functional MRI (rfMRI) signal. Under the proposal of Passingham et al (2002), previous studies have utilized structural connectivity (Johansen-Berg et al 2004;Tomassini et al 2007;Beckmann et al 2009;Saygin et al 2011a) or functional connectivity (Cohen et al 2008;Gordon et al 2016) to characterize the boundary of functionally distinct brain regions, or have utilized structural connectivity (Saygin et al 2011b;Osher et al 2016;Saygin et al 2016;Wu et al 2020) or functional connectivity (Tavor et al 2016;Parker Jones et al 2017) to predict the functional activation information of brain regions at various task states.…”
Section: Introductionmentioning
confidence: 99%